Quality Education Plays A Central Role in Shaping A Superior and Competitive Generation - M. Panji Wahyu Mukti; Agus Cahyono; Suwardi Suwardi (International Conference on Science, Education, and Technology, 2023)
Quality education plays a very important central role in shaping a superior and competitive generation. A quality education provides individuals with the necessary knowledge, skills and attitudes to face the challenges of a complex and globally connected modern world. In addition, quality education also shapes character, understanding of global issues, encourages innovation and improves quality of life. Therefore, serious investment in quality education is essential to create an excellent and competitive generation for the future. In this article, we will explore some of the reasons why quality education has a significant impact in shaping an excellent and competitive generation.